2013
DOI: 10.1111/j.1743-6109.2012.03004.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sexual Life of Women on Oral Contraceptive Continued-Regimen: Pilot Study

Abstract: Introduction To date, women may use flexible oral contraceptive (OC) regimens. Aim The aim of this study was to evaluate the quality of sexual life of healthy women on continued-regimen OCs. Methods Fifty women (age range 18–38) were enrolled. The Female Sexual Function Index (FSFI) and the Short Form-36 (SF-36) questionnaires were used to investigate, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
3
18
0
2
Order By: Relevance
“…Extended-cycle regimens significantly reduce use of menstrual-hygiene products and drug products to treat menstrual symptoms and may produce cost savings related to reduced work/school absenteeism and reduced doctor visits [ 26 ]. The potential benefit of extended-cycle regimens on sexual behavior and satisfaction requires further study but improvement has been suggested with a 72/4 COC regimen [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extended-cycle regimens significantly reduce use of menstrual-hygiene products and drug products to treat menstrual symptoms and may produce cost savings related to reduced work/school absenteeism and reduced doctor visits [ 26 ]. The potential benefit of extended-cycle regimens on sexual behavior and satisfaction requires further study but improvement has been suggested with a 72/4 COC regimen [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several recently well‐performed published studies, Italian researchers assessed female sexual function using the non‐validated FSFI Italian translation [20–24]. In consideration of the significantly increasing attention being given to female sexual function, it was mandatory to develop a complete validation of the Italian version of FSFI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent OCs are equally effective for birth control and, in general, have both good cycle control and tolerability [5–7]. However, the hormonal components of OCs could have various effects on mood and libido [8–14]. Although the reduction of circulating androgens levels and the loss of estrogen fluctuations may decrease sexual desire and vaginal lubrication, Sabatini and Cagiano demonstrated that these sexual negative effects progressively decrease and, in general, disappear by cycle 12 [15].…”
Section: Introductionmentioning
confidence: 99%